Live and die in East LA [videorecording (DVD)] - LaSardo, Robert, 1963-; Cabral, Richard, 1984-; Garcia, Cesar (Dreamscape Media, 2026)
After an E.R. doctor treats an injured boy, he is pulled into the world of gangs and street violence in the underbelly of Los Angeles.